Therapeutic efficacy of Pudilan Xiaoyan Oral Liquid (PDL) for COVID-19 in vitro and in vivo (2020)
Dear Editor, Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has rapidly swept through the worldwide, with more than 3 million confirmed cases. Until now, no vaccine or effective therapeutic measures are provided to prevent the SARS-CoV-2 infection. Existing medicines have some strong advantages on pharmacokinetics, known side effects, safety and dosing regimens.1 Although remdesivir and chloroquine could effectively inhibit the replication of SARS-CoV-2 in vitro,2 no medicine candidates have been evaluated in vivo by using animal models with SARS-CoV-2 infection.